The effect of deliberate practice in racket sports - Pearce, A. (2002)
This study was completed at the Department of Clinical Neurophysiology in the Australian Neuromuscular Research Institute as part of Dr Pearce's doctoral research studies investigating the human neuro-muscular system with transcranial magnetic stimulation (TMS) under a variety of movement types, including skilled vs. unskilled movement. The paper summarises a study conducted on athletes after the 1996 Olympic games. Investigations centred on the neuro-muscular effects on racket sport athletes who were refining their skills using a variety of practice methods, including match play, drill practice and to a lesser extent, repetition, on a daily basis, for international play.